It's our club! From supporter psychological ownership to supporter formal ownership. Issue 3 (June 2019) - Cocieru, Ovidiu C.; Delia, Elizabeth B.; Katz, Matthew
Highlights: Psychological ownership is a key contributing factor to fans becoming team owners. Fan ownership initiatives follow a pattern of events. Dissatisfaction with team management and trigger events determine fans to act. Actions taken by supporters involved in shareholder initiatives impact other fans. Abstract: A major development in international sport governance is the increasing number of clubs owned by supporters. Researchers have advocated for more supporter involvement in the governance of sport teams but have not fully explained why some supporters attempt to become team owners. Sport governance scholars have also generally ignored the perspectives of those fans that do not seek to become club owners. In the current study, the authors took the perspective of psychological ownership theory and used semi-structured interviews to examine the perspectives of a professional football team's supporters, some of which were interested in becoming team shareholders. The authors found that a primary reason supporters attempt to become club owners lies in their sense of psychological ownership for their team. Following this sense of ownership, supporter ownership initiatives appear to follow a certain pattern of events, including a sense of dissatisfaction, expressing such dissatisfaction in an attempt to bring about change, and eventually, initiating a formal ownership movement after reaching a tipping point. Lastly, the authors found that during supporter ownership movements, the actions taken by supporters involved in such initiatives may impact fans not involved in the ownership movement. The study makes contributions to sport governance, fan behavior, psychological ownership and fan social network literatures.